Combination of transfemoral balloon-assisted tracking and the knuckle wire technique as a solution in a challenging urgent percutaneous coronary intervention. Issue 7 (July 2019) - Talanas, Giuseppe; Corda, Giulia; Siciliano, Roberta; Murgia, Alessandro; Parodi, Guido
Abstract : Supplemental Digital Content is available in the text